Figur Ayah dalam Keluarga Kristen sebagai Teladan Membentuk Kepemimpinan Remaja di Era Teknologi Society 5.0 - Emmanuel, Joshua; Hermanto, Yanto Paulus; Prihanto, Joko (STTI Harvest Semarang, 2024)
Understanding the role of the father figure in the era of Society 5.0 technology in shaping leadership attitudes among adolescents requires an in-depth study. This research employs a qualitative method with a literature review approach to synthesize various theories on the exemplary role of fathers in fostering leadership qualities in adolescents. The findings of this study show that the exemplary character of a father is crucial in shaping adolescent leadership. A father’s example encourages adolescents to be less consumeristic and more adaptive in navigating situations amid technological advancements. Additionally, it fosters adolescents’ ability to make life choices, even in the face of negative influences in the Society 5.0 era. This study's results are essential to support fathers in setting a positive example for today’s youth. AbstrakKajian yang mendalam diperlukan dalam memahami figur ayah di era teknologi society 5.0 dalam membentuk sikap kepemimpinan dalam diri remaja. Penelitian ini menggunakan metode penelitian kualitatif, dengan pendekatan kajian pustaka dalam mensitesakan beberapa teori tentang keteladanan sosok ayah dalam membentuk kepemimpinan seorang remaja. Hasil penelitian ini menunjukkan bahwa keteladanan ayah dalam membentuk kepemimpinan remaja sangatlah penting. Keteladanan ayah akan menghasilkan remaja yang tidak konsumtif tetapi dapat menjadi adaptif dalam situasi yang dihadapi di tengah perkembangan teknologi. Disamping itu, mereka menjadi remaja yang dapat menentukan pilihan hidup, meskipun di tengah gempuran nilai-nilai yang negatif di era teknologi society 5.0. Hasil penelitian ini sangat penting menolong para ayah memberi teladan bagi anak remaja masa kini.